Accurate measurement of the force sensor for intermediate and proximal phalanges of index finger - Wan Khairunizam, Wan Ahmad, Dr.; Shahriman, Abu Bakar, Dr.; Nazrul H., Adnan (Foundation of Computer Science, 2012)
Link to publisher's homepage at http://www.fcsresearch.org/